1990
DOI: 10.1111/j.1751-908x.1990.tb00071.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Devonian Ohio Shale SDO‐1 as a USGS Geochemical Reference Sample

Abstract: Recommended concentrations for 38 elements in the U.S. Geological Survey reference sample, Ohio Shale (Devonian) SDO‐1, are presented here. For an additional 25 elements, average concentrations or ranges are reported for information. Also presented are the supporting analytical data and a description of the statistical procedure used in deriving recommended concentrations from that data. The sample is a brownish‐black, fissile, platy shale containing flattened pyrite nodules and a high organic content. It is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…The M-1 breccia data were all obtained in a single batch. With the M-1 batch of MIS samples, a single sample of USGS geochemical reference standard SDO-1 (shale, Devonian, Ohio) was run as a quality-control check (Table 1); our results agree well with the values recommended by Kane et al (1990).…”
Section: Trace Elementssupporting
confidence: 74%
“…The M-1 breccia data were all obtained in a single batch. With the M-1 batch of MIS samples, a single sample of USGS geochemical reference standard SDO-1 (shale, Devonian, Ohio) was run as a quality-control check (Table 1); our results agree well with the values recommended by Kane et al (1990).…”
Section: Trace Elementssupporting
confidence: 74%
“…Stibnite occurs in the form of columnar and radiating aggregates distributed in a darkgray chert (Fan et al 2004). The ores are characterized by a very high content of Sb -121,570-fold higher than the levels found in its continental crust (Taylor 1964;Taylor and McLennan 1985), 5930-fold higher than the levels found in Devonian Ohio Shale (Kane et al 1990) and 4863-fold higher than those found in average black shale (Yudovich and Ketris 1994).…”
Section: Field Sites and Sample Collectionmentioning
confidence: 96%
“…(Olcott 1995). Some shales can have high S contents; for e.g., the Devonian Shale in Ohio (Kane et al 1990) has been reported to contain 5.35% S by weight. The parent material was derived from glacial till (Kent Drift of Woodfordian formed 19,000 y B.P.)…”
Section: Introductionmentioning
confidence: 99%